Application of Capillary Irrigation Systems on Land (Paddy Field Soil, Field Soil and Farm Soil) - Rahmania, Syiffa; Candra, Aldo Deska; Zulfakri, Zulfakri; Surya, Satria Adi (ITScience (Information Technology and Science), 2025)
Capillary irrigation utilizes water from a water source to a reservoir, where plants absorb it through a wick. Soil porosity is a functional space connecting the soil body with its environment. Water loss is a complex phenomenon in a water distribution system that refers to the volume of water lost between the production source and the point of consumption. Moisture content is the amount of water contained in a material and is expressed as a percentage of the material's wet or dry weight. The capillary irrigation system was designed using a 1.5 L aqua bottle and flannel cloth as a water delivery medium with varying cloth placement depths (2 cm, 4 cm, and 6 cm). This system was applied to paddy fields, farms, and field soil. The parameters observed included soil porosity, moisture content, and water loss. Based on the study's results, farm soil had the highest porosity with an average of 81.3%, followed by field soil at 77.7% and paddy soil at 75.3%. The results of moisture content observations show that farm soil has the highest moisture content with an average of 94.67%, followed by paddy soil at 77.38% and field soil at 68.17%. Based on weekly water volume data, farm soil has the highest average water volume at each axis depth, followed by field soil, and the lowest is paddy soil. Capillary irrigation works effectively. Farm soil has the highest porosity and moisture content and is best for aeration and drainage.